Development of Barium Strontium Titanate (BST) Based Sensor/ Instruments - Johari, Adnan, Assoc. Prof. Dr.; Zul Azhar, Zahid Jamal, Prof. Dr.; Irzaman Sulaiman, Hussain, Dr.; Sanna, Taking; Mohd Asri, Idris; Nurjuliana, Juhari; Norhayati, Sabani (Malaysian Invention and Design Society (MINDS), 2010)
Assoc. Prof. Dr. Johari Adnan and his team from School of Microelectronic Engineering won silver for Development of Barium Strontium Titanate (BST) based Sensors/Instruments. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.